What Do Micro Price Data Tell Us on the Validity of the New Keynesian Phillips Curve? - Luis J. Álvarez (Kiel Institute for the World Economy (IfW), 2007)
The New Keynesian Phillips curve (NKPC) is now the dominant model of inflation dynamics. In recent years, a large body of empirical research has documented price-setting behaviour at the individual level, allowing the assessment of the micro-foundations of pricing models. This paper analyses the implications of 25 theoretical models in terms of individual behaviour and finds that they considerably differ in their ability to match the key micro stylised facts. However, none is available to account for all of them, suggesting the need to develop more realistic micro-founded price setting models.
Keywords: D40; E31; 330; Pricing models; micro data; Phillips Curve; hazard rate